Measurement of Information System Quality Management using ISO 9001:2015 Standards at PT Bersama Kita Besar - Adrianus Kelvin; Wella Wella (Universitas Islam Raden Rahmat, Malang, 2024)
Operational problems related to performance evaluation within the company are the background for this research. Data was collected through interviews with the chief auditor, a 4-item questionnaire for the head of IT and 3 IT staff, and observations of company documents and staff performance. The questionnaire used a Likert scale, and the overall assessment applied the Maturity Model. Results indicated that PT. Bersama Kita Besar achieved a level 3 (Defined Process) in maturity. Small improvements are needed to reach levels 4 and 5, such as enhancing staff performance through training and adding competent human resources. The study focused on the IT division of PT Bersama Kita Besar, using clauses 4 to 10 of ISO 9001:2015 for measurement. These results can support the company's ISO 9001:2015 certification efforts and ongoing improvements.